FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG DISMINOREA - Mulyana, Desi Nurlaela; Indriyani, Devia (MIDWIFERY JOURNAL, 2021)
Dysmenorrhea is a symptomatic phenomenon that includes abdominal pain, cramps, and back pain. Gastrointestinal symptoms such as nausea and diarrhea may occur as a symptom of menstruation. The purpose of this study was to determine the factors associated with the level of knowledge of young women about dysmenorrhea in RT 001, Kp. Tambun Kapling, Setia Pahlawan Village, Tarumajaya District, Bekasi Regency in 2020.The research is descriptive quantitative analysis, the sample in this study were 38 young women, data collection by distributing questionnaires and analyzed using Chi Square test.From the results of the research, there were 15 girls (39.5%) with good knowledge, 23 people (60.5%). And among the variables of menarche age at >12 years (57.9%) <12 years 16 (42.1%), sources of information through electronic media 22 (57.9%) non-electronic media 16 (42.1%), the role of parents are quite 27 (71.1%) good 11 (28.9%), and the nutritional status of thin 9 (23.7%) normal 29 (76.3%) .The results of the analysis of this study showed that there was no relationship between age, source of information and nutritional status with knowledge, but there was a relationship between the role of parents and the knowledge of adolescent girls about dysmenorrhea, from the analysis results obtained OR = 2.1 (95% CI: 0.463- 9,839) adolescents with "enough" parental roles are at risk of lacking knowledge of dysmenorrhea 2.1 times compared to adolescents with "good" parenting roles.The conclusion is that there is no relationship between age, source of information and nutritional status on adolescent knowledge, but there is a relationship between parental roles and knowledge of young women about dysmenorrhea. the role of "good" parents .It is recommended to young women, in order to increase knowledge about dysmenorrhea through media and non-media and increase the role of parents who have young women to increase their knowledge.. Keywords: Dysminorrhea, adolescent girls ABSTRAKDisminorea merupakan suatu fenomena simpomatik yang meliputi nyeri abdomen, kram, dan sakit punggung. Gejala gastroinstetinal seperti mual dan diare dapat terjadi sebagai gejala menstruasi. Tujuan Penelitian ini adalah Untuk mengetahui faktor-faktor yang berhubungan dengan tingkat pengetahuan remaja putri tentang disminorea di RT 001, Kp. Tambun Kapling, Desa Pahlawan Setia, Kecamatan Tarumajaya, Kabupaten Bekasi Tahun 2020.Penelitian bersifat analisis deskriptif kuantitatif, sampel dalam penelitian ini adalah 38 remaja putri, pengambilan data dengan cara membagikan kuesioner serta di analysis menggunakan uji Chi Square.Dari hasil penelitian remaja putri yang berpengetahuan baik yaitu 15 orang (39,5%) berpengetahuan kurang yaitu 23 orang (60,5%). Dan diantara variabel usia menarche pada >12 tahun (57,9%) <12 tahun 16(42,1%), sumber informasi melalui media elektronik 22 (57,9%) non media elektronik 16(42,1%), peran orangtua cukup 27(71.1%) baik 11(28,9%), dan status gizi kurus 9(23,7%) normal 29(76,3%).Hasil analisis penelitian ini menunjukkan tidak ada hubungan anatara usia, sumber informasi dan status gizi dengan pengetahuan, akan tetapi ada hubungan antara peran orangtua dengan pengetahuan remaja putri tentang disminorea, dari hasil analisis diperoleh nilai OR= 2,1 (95% CI: 0,463-9,839) remaja dengan peran orangtua “cukup” beresiko kurang pengetahuan disminorea 2,1  kali dibandingkan remaja dengan peran orang tua “baik”.Kesimpulan tidak ada hubungan anatara usia, sumber informasi dan status gizi terhadap pengetahuan Remaja, akan tetapi terdapat hubungan antara peran orangtua dengan pengetahuan remaja putri tentang disminorea, remaja putri dengan peran orangtua “cukup” beresiko kurang pengetahuan tentang disminorea 2,1  kali dibandingkan remaja dengan peran orang tua “baik”Disarankan kepada remaja putri, agar dapat meningkatkan lagi pengetahuan tentang disminorea melalui media dan non media serta meningkatkan peran orang tua yang memiliki remaja putri untuk meningkatkan pengetahuannya.Kata Kunci : Disminorea, remaja putri